Dynamic stiffness identification methods: experimental study and validation - Slimane, Rabii; El Khatiri, Wafaa; Cherif, Raef; Atalla, Noureddine (Frontiers in Acoustics, 2023)
In a vehicle, the operation of mechanical systems generates undesirable vibrations and noise, and their reduction requires the study of three parts: vibrating systems, receiving structures, and connecting interfaces. The study presented in this paper concerns the connecting interfaces between subsystems. In particular, the in-situ characterization of the isolation interface between two substructures by measuring dynamic transfer stiffness. In contrast to current methods, which require the disassembly of the vibration isolator from its original assembly, in-situ methods have been studied and validated. This study sheds light on the strengths and limitations of each approach.These are known as the direct in-situ method (D-IS) and round trip in-situ method (RT-IS).Experimental validation has been carried out by comparing the D-IS method to the resonance method on a simple system. Good agreement is obtained between the two methods, making it possible to validate the method at low frequencies. Then, a comparison between the two methods D-IS and RT-IS is carried out on a more resonant test bench. The obtained stiffnesses were further validated using transfer path analysis (TPA) techniques to verify the performance of the proposed